RETRACTED: Waste Management in European Countries: Indicators, Clustering, and Socioeconomic Implications - Khomenko Liliia; Rosokhata Anna; Nesterenko Volodymyr (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002